Moving in a moving medium: new perspectives on flight - Emily Shepard (Philosophical Transactions of the Royal Society B: Biological Sciences, 2016)
One of the defining features of the aerial environment is its variability; air is almost never still. This has profound consequences for flying animals, affecting their flight stability, speed selection, energy expenditure and choice of flight path. All these factors have important implications for the ecology of flying animals and the ecosystems they interact with, as well as providing bio-inspiration for the development of unmanned aerial vehicles. In this introduction we touch on the factors that drive the variability in airflows, the scales of variability and the degree to which airflows may be predictable. We then summarise how papers in this volume advance our understanding of the sensory, biomechanical, physiological and behavioural responses of animals to air flows. Overall, this provides insight into how flying animals can be so successful in this most fickle of environments.